Analisis Hierarki Gramatikal pada Artikel Kompas.com - Abdul Latif; Nurkhumaira Tus Dayu (Faculty of Languages and Arts, Universitas Negeri Padang, 2023)
Kompas is one of the mass media that is still popular with news readers in Indonesia. In addition, there are still many writers who submit their writings to be published in the Kompas Opinion column. The grammatical hierarchy which includes syntax, morphology and phonology in Kompas.com articles needs to be examined to find out grammatical errors in a discourse (article). This study used a qualitative approach with a descriptive method aiming to identify how wrong the application of grammatical hierarchy was in the Kompas.com article published in May 2022. Errors in using grammatical hierarchy were recorded at the phonological level in the form of adding phonemes 14%; morphological level in the form of compounding 6%; syntax level in the form of using punctuation marks 8%, writing absorption elements 14%, using hyphens 6%, using words 46% and ineffective sentences 6%. The ineffectiveness of the dominant grammatical hierarchy is at the syntactic level.